2017
DOI: 10.1007/s00167-017-4495-9
|View full text |Cite
|
Sign up to set email alerts
|

Complete posterolateral meniscal root tear is associated with high-grade pivot-shift phenomenon in noncontact anterior cruciate ligament injuries

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…Clinically, the patterns of LMPR lesion are not so simple and present varying forms, from partial radial tears to complete root avulsions. 13,21 Song et al 35 compared the proportions of complete LMPR lesions in ACL-injured knees with different grades of pivot shift and demonstrated that a complete LMPR lesion was an independent risk factor of high-grade pivot shift, indicating the potential influence of different LMPR lesion patterns on dynamic knee instability. In cadaveric studies testing the kinematics of ACL-deficient knees, complete detachment of the LMPR root increased anterior tibial displacement of ACL-deficient knees during anterior loading and simulated pivot-shift loading.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically, the patterns of LMPR lesion are not so simple and present varying forms, from partial radial tears to complete root avulsions. 13,21 Song et al 35 compared the proportions of complete LMPR lesions in ACL-injured knees with different grades of pivot shift and demonstrated that a complete LMPR lesion was an independent risk factor of high-grade pivot shift, indicating the potential influence of different LMPR lesion patterns on dynamic knee instability. In cadaveric studies testing the kinematics of ACL-deficient knees, complete detachment of the LMPR root increased anterior tibial displacement of ACL-deficient knees during anterior loading and simulated pivot-shift loading.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the present study adds further elements to the original understanding of LMPR lesions and ATSLC in extension. 4,26,27,35,37 In ACL-deficient knees, the loss of the “wedge effect” maintained by the posterior horn of the lateral meniscus attributed to LMPR lesions decreases dynamic rotational stability, leaving those knees in a “resting pivoted position” under an unloaded state; thus, excessive anterior tibial subluxation was identified in the lateral tibiofemoral compartment. As greater ATSLC in extension may result in intercondylar notch impingement and chronic degeneration of the ACL graft because of the anterior shift of tibial tunnel 4,39 and as excessive ATSLC in extension could be a mechanistic rationale for the failed ACLR, 17,26,37 it is important to diagnose and surgically treat the LMPR lesion, especially the chronic root avulsion, to reestablish a normal tibiofemoral relationship in extension during ACLR for patients with high-grade ATSLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monaco et al [27] demonstrated that a grade III pivot shift is only seen in the absence of both the ACL and ALL in vitro. However, the potential confusing factors of a high-grade pivot shift, such as a lateral meniscus or root tear, ITB injury, or general hyperlaxity should be assessed [28,29].…”
Section: Diagnosismentioning
confidence: 99%
“…In addition, LMRT were significantly associated with a high-grade pivot-shift in noncontact ACL injuries (odds ratio, 4.044; 95% confidence interval, 1.125-14.534; P= 0.032). 48 …”
Section: Beyond the Alc: Other Contributions To Instability In The Acmentioning
confidence: 99%